Age and gender considerations on the symptomology in patients with superior semicircular canal dehiscence: A systematic review and case illustration. (July 2019) - Nguyen, Thien; Sheppard, John P.; Duong, Courtney; Ding, Kevin; Dejam, Dillon; Alkhalid, Yasmine; Romiyo, Prasanth; Azzam, Daniel; Prashant, Giyarpuram; Gopen, Quinton; Yang, Isaac
Highlights: A total of 18 retrospective studies involving 174 total patients undergoing SSCD repair were analyzed. Female patients showed significant improvement of hearing loss ( p = 0.01) compared to males following surgery. Prevalence and resolution of symptoms pre and post surgery were comparable between patients <65 years and ≥65 years. Abstract: Superior semicircular canal dehiscence (SSCD) is caused by a fistula in the arcuate eminence, creating vestibular and auditory disturbances. We aim to determine the effects of gender and age on symptom prevalence and resolution in patients with SSCD . A Boolean search was conducted through four separate scientific databases. Full-text English articles for SSCD patients, who underwent surgery were included. Demographics and outcomes were extracted. A total of 198 patients were identified, and available for quantitative analysis. Between genders, there were no differences in the prevalence of pre- or post-operative symptomology. Both genders had statistically significant improvement in symptomatology with females experiencing significantly high rates of hearing loss improvement compared to male patients. Compared to their younger cohort, patients over 65 had similar symptom frequencies before and after surgery with similar rates of symptom resolution. SSCD repair is safe and effective for resolving auditory and vestibular symptoms. Gender and age may not be strong predictors of patient presentation or symptom resolution. Gender and age-associated factors may not influence patient outcomes.